High performance web servers using load balancing technique / Siti Aishah Ab Rahman - Ab Rahman, Siti Aishah (Faculty of Information Technology and Quantitative Sciences, 2006)
A World Wide Web (WWW) Server is normally a single machine dedicated to process a HTTP request for a single WWW site. Web server serves web pages to clients across the Internet or an Intranet. The web server hosts the pages, scripts, programs, and multimedia files and serves them using HTTP, a protocol designed to send files to web browsers and other protocols. .In order to achieve web server scalability, more servers need to be added to distribute the load among the group of servers, which is also known as a server cluster. The load distribution among these servers is known as load balancing. Load balancing applies to all types of servers, the application server and database server. However, this project will be devoting this section for load balancing of web servers (HTTP server) only. Load balancing is a technique that distributes processing and communications activity evenly across a computer network so that no single device is overwhelmed. In other words, when multiple web servers are present in a server group, the HTTP traffic needs to be evenly distributed among the servers. The purpose of load balancing was done due to the increases of traffic, complexity of the application software and to satisfy the critical online transaction nowadays. The overall exact nature of this project is a setup of load balancer, a cluster of real servers and clients. The architecture of the cluster is transparent to clients outside the cluster. Client applications interact with the cluster as if it were a single high-performance and high available server. Clients will not be affected by interaction with the cluster and do not need modification. The load balancing method used in this project is Round Robin Scheduling that distributes job or request equally among the web servers. The Round Robin method that will be use in this project is dispatcher-based load balancing cluster where the parallel services of servers can appear as a virtual service on a single IP address. For routing, Network Address Translation is a technique in which the source or destination addresses of IP packets are rewritten as they pass through a router or firewall.